A distinct subclade of AlkB family demethylases in ciliates safeguards the positional fidelity of eukaryotic N 6 -methyladenine (6mA) - Junhua Niu; Haoze Yu; Yongqiang Liu; Lanheng Nie; Bei Nan; Wenxin Zhang; Ni Song; Shaoqin Rong; Dan Zhou; Shan Gao (Proceedings of the National Academy of Sciences, 2026)
DNA N 6 -methyladenine (6mA) is a newly recognized transcription-associated epigenetic mark in eukaryotes. While its methylation pathway has been well established, the identity of eukaryotic 6mA demethylase(s) responsible for its removal and dynamic regulation has remained elusive. Here, we identify and characterize DMT3 (TtALKBH5), an AlkB family dioxygenase in Tetrahymena thermophila , as a 6mA demethylase in ciliates and potentially several other unicellular eukaryotes with abundant 6mA and a defined AMT1 methyltransferase (MTase) complex, supported by genetic and molecular evidence. DMT3 acts on both fully and hemimethylated ApT dinucleotides, an activity partially facilitated by a naturally occurring cysteine-to-serine substitution. Genome profiling shows that DMT3 is enriched at transcription start sites (TSSs) of 6mA-enriched genes, complementary to the occupancy pattern of the AMT1 complex, where it selectively removes spurious 6mA deposited by AMT1. Genetic disruption of DMT3-mediated demethylation, either by knockout or catalytic inactivation, leads to aberrant 6mA accumulation at TSS regions, transcriptional dysregulation, altered chromatin accessibility, and impaired initiation of sexual reproduction. Notably, simultaneous removal of DMT3 and AMT1 eliminates these defects, indicating that spurious TSS 6mA underlies transcriptional and developmental impairment.